miR‐130a‐3p enhances autophagy through the YY1/PI3K/AKT/mTOR signaling pathway to regulate macrophage polarization and alleviate diabetic retinopathy - Xiaoting Xi; Xuewei Wang; Jia Ma; Qianbo Chen; Yuxin Zhang; Yaxian Song; Yan Li (Journal of Diabetes Investigation)
ABSTRACT Aims/Introduction Diabetic retinopathy (DR) is a common complication of diabetes that can lead to poor vision and blindness. This study aimed to explore the mechanism of action of miR‐130a‐3p in DR progression. Materials and Methods In this study, we administered a single intraperitoneal injection of 100 mg/kg streptozotocin (STZ) to construct a DR mouse model, and induced a human monocyte cell line (THP‐1) to differentiate into M0 macrophages, after which the M0 macrophages were cultured with 30 mM high glucose (HG) as a model of inflammation. The relative gene and protein levels were validated by RT–qPCR and western blotting. Macrophage polarization and retinal damage in the mice were tested using ELISA, MDC staining, immunofluorescence staining, and HE staining. Results The results revealed that the expression of miR‐130a‐3p was low in M1 macrophages, whereas the expression of miR‐130a‐3p was high in M2 macrophages, and the level of miR‐130a‐3p was reduced after HG treatment of macrophages. The overexpression of miR‐130a‐3p attenuated HG‐ or STZ‐induced inflammation, promoted macrophage autophagy, inhibited M1 polarization of macrophages, and attenuated the progression of DR. In addition, YY1 was the downstream target gene of miR‐130a‐3p, and overexpression of miR‐130a‐3p inhibited YY1 expression. However, overexpression of YY1 weakened the effect of miR‐130a‐3p mimic. After further treatment with the PI3K/Akt/mTOR pathway activator 740 Y‐P, the effect of YY1 knockdown was weakened, macrophage autophagy was inhibited, and M1 polarization and inflammation were promoted. Conclusion miR‐130a‐3p inhibited the activation of the PI3K/Akt/mTOR pathway by downregulating YY1 expression, thus facilitating macrophage autophagy, inhibiting M1 polarization and the inflammatory response of macrophages, and finally attenuating the progression of DR. The results of this study provide theoretical support for the use of miR‐130a‐3p as a new target for the treatment of DR.